Dead fall [large type] - Mehl, Nancy (Mehl, Nancy. Quantico files, 2022)
"After putting to rest the most personal case of her career, Alex Donovan is ready to move on and focus on her future at the FBI's elite Behavioral Analysis Unit. When the BAU cofounder is discovered dead in his hotel room, the FBI is called in to work on the strangest case they've ever faced. How do you find a killer who murders his victims from a distance? When it becomes clear that the killer is targeting agents in Alex's unit, they are ordered into lockdown, sheltered in the dorms at Quantico. Alex bunks with controversial agent Kaely Quinn, and as they work together, Alex discovers in Kaely the role model she's never had - despite being warned away. As Alex questions the type of agent she wants to become, things get personal when the brilliant killer strikes close to home. Now Alex will do anything to find the killer - even at the risk of her own life."--